Progressive multifocal leukoencephalopathy following fludarabine treatment in a chronic lymphocytic leukemia patient - Lejniece, S.; Murovska, M.; Chapenko, S.; Breiksa, B.; Jaunmuktane, Z.; Feldmane, L.; Ziedlina, I.; Gomez-Roman, J.; Garcia-Cabeza, M.; Lejnieks, A. (Experimental Oncology, 2011)
Progressive multifocal leukoencephalopathy (PML) is a neurological disease caused by infection of the central nervous system (CNS) with the JC polyomavirus (JCV). JCV is endemic and infects a large proportion (70–90%) of healthy individuals worldwide, but infection is latent. JCV reactivation may occur, if the immune function is compromised. Aim: To present a PML case in a CLL patient after a long course of disease and treatment with fludarabine. JCV virus infection in this patient was proven both in brain biopsy material and blood. Methods: Patient with a nine-year history of CLL was hospitalized with the weakness in the right leg and left hand, tremors, speech difficulties. An MRI diagnosed infiltrative glial tumor of the left hemisphere, proliferating predominantly in the frontal lobe, more in the gyrus frontalis superior region. CNS tumor biopsy performed. Results: Morphology and immunoprofile of the lesion consistent with progressive multifocal leukoencephalopathy. The material from biopsy was diagnosed as positive for JCV DNA. JCV and HHV-7 genomic sequences were found in patient’s PBL DNA sample. In a plasma DNA sample, only genomic sequences were detected. Conclusion: The present case draws attention to the fact that the use of fludarabine and its combinations in CLL therapy increases the risk of JCV infection reactivation and development of serious complications like PML.